Rule of Prebiotics Comprising Infant Formula in Treatment of Acute Diarrhea (Eurasian Medical Research Periodical, 2022)
Acute diarrhoea is a major contributor to infant morbidity and death. Prebiotics are indigestible dietary components that promote the development of beneficial microorganisms like bifidobacteria.